Effects of Walnut Leaf Extracts Prepared in Different Solvents on Seed Germination and Seedling Growth of Cress (Lepidium sativum cv. Zeybek) - Kocacaliskan, Ismail; Kilic, Berna; Terzi, Irfan (FERDINAND BERGER SOEHNE, 2015)
In this study, effects of walnut leaf extracts prepared in six different solvents water, ethanol, methanol, aceton, tetrahydrofuran (THF) and dimethyl sulfoxide (DMSO) on seed germination and post-germinative seedling growth of cress (Lepidium sativum L. cv. Zeybek) have been investigated. All the treatments were seen to inhibit germination percentage of the seeds in second day, whereas only DMSO and methanol extracts inhibit it in fifth day. DMSO and methanol extracts decreased germination rate of the seeds significantly with respect to control, as well. Both root and shoot elongation were inhibited by the treatments of DMSO, water and methanol extracts in range of effectiveness grade from high to low. While shoot fresh weight was decreased by all the treatments, root fresh weight was decreased only by DMSO, water and methanol extracts. Among the treatments, the most strong inhibitory effect was found to have DMSO extract on both seed germination and seedling growth parameters. Thus, it was discussed in the manuscript that DMSO may be more efficient and proper solvent in preparation of walnut leaf extract.
Keywords: Cress; seed germination; seedling growth; solvents; walnut leaf extracts; JUGLANS-MANDSHURICA-MAXIM; JUGLONE; APOPTOSIS; Plant Sciences